Políticas de acesso e permanência no ensino básico da Guiné-Bissau: um estudo de caso da escola da região de Biombo Domingos Britos dos Santos - Djedju, Morida (2024)
This master's dissertation is entitled Access and Permanence Policies in Basic Education in Guinea-Bissau: a case study of the Biombo Domingos Britos dos Santos School in the Region and is linked to the Public Policies, Educational Practices and their Interfaces Research Line of the Postgraduate Program in Education at the Federal University of Santa Maria. Its objective is to understand to what extent Guinean educational policies enhance students' access and permanence in basic education at the Biombo Domingos Britos dos Santos school in the region. The work is based on the following authors: Lourença Ocuni Cá (2005), João Huco Monteiro (2007), Maria Odete Semedo (2018), Fernando Siga (2020), Stephen Ball (2011) among others. Understanding educational policies in Guinea-Bissau, especially in the Biombo/Quinhamel region, leads us to look at its pre-colonial, colonial and post-colonial past, because only in this way will we be able to understand the government initiatives and strategies that aim to promote access to education and ensure the permanence of students in basic education institutions in the country. Guinea-Bissau has faced significant challenges over time in the search for quality education and opportunity for all. Given this, the research is guided by the following problem: To what extent do Guinean educational policies enhance the access and permanence of basic education students in schools in the Biombo Domingos Britos dos Santos region? In order to answer the central question of the research, we sought to understand the impact of educational policies aimed at access to and retention in Basic Education in the school mentioned above. Regarding the methodological paths, we based ourselves on the qualitative approach, conducting a case study in the context of the school in the Biombo Domingos Britos dos Santos region. In short, the analysis of the data is based on the understanding of Guinean educational policies considering the critical analysis present in the discourses of the social actors who constitute the aforementioned school. Based on the critical analysis of the content of the discourses, we aim to produce meanings about the challenges and advances in the implementation of access and retention policies in Guinea-Bissau. On the other hand, the study highlights the relevance of the State in assuming a promising commitment to education for the entire Guinean population and especially in Basic Education, through investment in infrastructure, programs that guide the development of quality education adapted to the local reality and training of teachers who work in basic education.